Relational Contracts with Private Information on the Future Value of the Relationship: The Upside of Implicit Downsizing Costs - Matthias Fahn; Nicolas Klein (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyze a relational contracting problem, in which the principal has private information about the future value of the relationship. In order to reduce bonus payments, the principal is tempted to claim that the value of the future relationship is lower than it actually is. To induce truth-telling, the optimal relational contract may introduce distortions after a bad report. For some levels of the discount factor, output is reduced by more than would be sequentially optimal. This distortion is attenuated over time even if prospects remain bad. Our model thus provides an alternative explanation for indirect short-run costs of downsizing.
Keywords: C73; D86; 330